Moldylocks and the three beards - Jones, Noah (Noah Z.) (New York, NY Scholastic Inc, 2014)
After falling through the refrigerator into the Land of Fake Believe, Princess meets a girl named Moldylocks who takes her to the home of the Three Beards for chili--but when the Beards capture her friend, Princess must come up with a plan to save her
English stories
Reading level grade 2
Appeals to 1st-2nd graders
1 13
Keywords: Fairy tales; Humorous stories; Fairy tales; Humorous stories